(untitled) (Sagasteguiana, 2017)
D. caryophyllus “clavel” es una planta ornamental que contribuye con el 12% de la exportación de flores a nivel mundial y se hace necesario masificar su cultivo utilizando los cultivo in vitro. Por ello se experimentó evaluar la germinación en condiciones in vitro en tres diferentes medios de cultivo. Los tratamientos fueron el medio de Murashige y Skoog (MS), medio con agua de coco y medio con extracto de papa, se compararon el porcentaje de germinación (%G), la velocidad de germinación (M) e índice de germinación (IG). El análisis estadístico del número de semillas germinadas al sexto día de siembra mostró que el medio agar con agua de coco (AC) fue el más efectivo para la germinación del clavel siendo estadísticamente similar al medio MS y distinto del medio con extracto de papa que obtuvo los valores más bajos. Palabras clave: germinación, D. caryophyllus, medio de cultivo. ABSTRACT D. caryophyllus "carnation" is an ornamental plant that contributes with 12% of the export of flowers worldwide and it is necessary to massify its cultivation using the in vitro culture. Therefore, it was experimented to evaluate the germination in in vitro conditions in three different culture media. The treatments were the medium of Murashige and Skoog (MS), medium with coconut water and medium with potato extract, the percentage of germination (% G), germination speed (M) and germination index (GI) were compared. . The statistical analysis of the number of seeds germinated on the sixth day of sowing showed that the agar medium with coconut water (AC) was the most effective for germination of the carnation being statistically similar to the MS medium and different from the medium with potato extract that obtained the lowest values. Key words: germination, D. caryophyllus, culture medium.